Effectiveness of Vestibular Stimulation Training in Cerebral Palsy (Medico Legal Update, 2020)
Introduction: Various studies are carried out to improve posture and balance in children with cerebralpalsy by using different approaches. But the aspect of vestibular stimulation exercises on improving postureand balance in children with CP have not yet been studied. Hence this study is design to see the effect ofvestibular stimulation exercises on posture and balance in children with CP.Methodology: Thirty children with clinical diagnosis of Cerebral palsy, were randomly allocated into controlgroup and interventional group. Participants in control group were given Conventional Physiotherapy.Participants in intervention group were given Conventional Physiotherapy and vestibular stimulationexercises.Results: The result of the study found extreme significant effects of the conventional physiotherapy incontrol group and extreme significant effects of conventional physiotherapy and vestibular stimulationexercises on posture and balance in children with CP in intervention group according to the results of theGMFM-88 and PBS. There is significant difference in mean score of GMFM-88 and PBS in interventiongroup as compared to the control group.Conclusion: There will be significant effect of vestibular stimulation exercises on posture and balance inchildren with CP.